"Shot to the Heart": Case Report and Concise Review of Cardiac Gunshot Injury. (August 2020) - Kawall, Tiffany; Seecheran, Rajeev Virender; Seecheran, Valmiki Krishna; Persad, Sangeeta Anjali; Jagdeo, Cathy-Lee; Seecheran, Naveen Anand
Penetrative cardiac injury can often result in life-threatening sequelae such as myocardial contusion or rupture, coronary vessel and valvular damage, pericardial effusion with tamponade, and arrhythmias of which gunshot injury is a chief culprit. We report a case of a suspected acute coronary syndrome after a cardiac gunshot injury that was conservatively managed.